Development of Social Studies Learning Module Based on Problem Based Learning with Outdoor Study to Improve Learning Outcomes of 7th Grade Junior High School Kesatrian 1 Students - Rahman, Abdul Haris Bahtiar; Wasino, Wasino; Martitah, Martitah (Universitas Negeri Semarang, 2018)
The main problem of social studies learning in Junior High School Kesatrian 1 is that many students are less interested and feel bored when following social studies learning. This has a direct impact on students learning outcomes. Teaching materials used in learning also do not guide students to solve problems. Therefore, it is necessary to research and develop teaching materials that can guide students to solve problems so that the students’ learning outcomes and motivation are increased. The purpose of this research is (1) to analyze the problems of social studies learning in 7th grade Junior High School, (2) compiling social studies learning module based on Problem Based Learning with Outdoor Study, (3) analyzing the effectiveness of the results of the development of learning modules based on Problem Based Learning with Outdoor Study. The research approach used is Research and Development. Data collections are including interviews, observation, study of documents, questionnaires and tests. Data analysis of this research includes descriptive data analysis and quantitative descriptive data analysis. The research findings showed that (1) social studies learning in Junior High School Kesatrian 1 showed that many students felt bored following social studies learning which had an impact on low learning outcomes. Teaching materials that are used did not guide the students to solve the problems. (2) The development of learning modules is carried out in seven stages (3) The social studies learning module based on Problem Based Learning with Outdoor Study is effectively used for social studies learning.